Defect‐Based Single‐Atom Electrocatalysts. Issue 9 (20th December 2018) - Zhang, Yiqiong; Guo, Lan; Tao, Li; Lu, Yanbing; Wang, Shuangyin
Abstract: Single‐atom catalysts (SACs) have attracted great attention owing to their maximum atomic utilization and high catalytic performance in electrochemical reactions. But the synthesis of SACs is not easy due to large surface energies of single atomic metal sites which often lead to their aggregation. The defects on supports can serve as anchor sites to stabilize single metal atoms and prevent them from aggregation, which has become an effective method to fabricate SACs. This review summarizes the meaningful findings about the defects on supports stabilizing single metal atoms, and their applications in electrocatalytic reaction. Various defects, including the intrinsic defects or heteroatom doping of carbon‐based materials, cation or anion vacancies of metal compound supports, and other defects (step edges, lattice defects, and caves), are comprehensively summarized, and the effects of defects on designing SACs are discussed. Although there are still many challenges to fully explore the SACs, it is believed that the newly established defect sites stabilized single atoms mechanism will be helpful for designing and fabricating highly powerful single atomic electrocatalysts for practical applications. Abstract : This review focuses on the defects on supports to design stable single‐atom catalysts and their applications in electrocatalytic reaction. Various defects including the intrinsic defects or heteroatom‐doped of carbon‐based materials, cation or anion vacancies of metal compound supports, and other defects (step edges, lattice defects, and caves) are systematically summarized, and the effects of defects on designing SACs are discussed.